Application of herbal probiotics in feed on growth and blood profile of elver eels (Anguilla bicolor McClelland, 1844) - Harun Harun; Muamar Abdan; Suprihadi Suprihadi; Fazril Saputra; Kharunnisak Kharunnisak; Said Samsuli; Rahmat Sulni (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Shortfin eel cultivation in Indonesia has shown significant development in aquaculture. However, various challenges still hinder its successful implementation. This study aims to investigate the impact of herbal probiotics on the growth and blood profile of elver eels (Anguilla bicolor). The research was conducted at UPR Mina Mandiri in the Beutong District of Nagan Raya Regency, from August to October 2022This research was conducted at UPR Mina Mandiri, Beutong District, Nagan Raya Regency, from August to October 2022. A Completely Randomized Design (CRD) with five treatment levels and three replications was employed for this study. The treatments consisted of herbal probiotics added to the eels' feed: 0, 15, 20, 25, and 30 ml/kg. The data obtained from the experiment were subjected to an analysis of variance (ANOVA) to assess the significance of the results. ANOVA test results show that probiotics significantly affect survival rate, absolute weight growth, specific weight rates, feed efficiency, and the elver eel blood profile (hemoglobin, erythrocytes, and leukocytes). (P0.05). Duncan's advanced test revealed significant differences in the growth parameters and blood profiles among the various treatments. Treatment B, which utilized a dosage of 15 ml/kg of feed, displayed the most favorable outcomes. It achieved a survival rate of 93.33%, absolute weight growth of 2.69 grams, a specific growth rate of 1.73%, and a feed efficiency of 48.56%. Additionally, the blood profile measurements for treatment B were as follows: hemoglobin levels ranged from 9.53 to 9.73 g/dl, erythrocyte count ranged from 1.12 to 1.23 x 103 cells/mm3, and leukocyte count ranged from 120 to 133 x 103 cells/mm3.Keywords:blood profilefish healthgrowthshortfin eels probiotics